REPRESENTATION AND PERFORMANCE ANALYSIS OF MANUFACTURING CELL BASED ON GENERALIZED STOCHASTIC PETRI NET - Seo, YoonHo; Kim, Taioun; Kim, ByungNam; Sheen, DongMok (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
To achieve high flexibility and agility for rapidly changing customer’s demand, Petri net has been adopted as a modeling and performance analysis tool. The Purpose of this paper is to propose modeling and performance analysis schemes of flexible manufacturing line using a generalized stochastic Petri net. The manufacturing line can be represented using workflows which are composed of bill of material and processes. Bill of process shows the precedence of processes and the relationship among the manufacturing and assembly operations. An algorithm generating a Petri net from bill of material database is proposed. The scheme of generalized stochastic Petri net utilizing both immediate and exponential distributed transitions are adopted to model a manufacturing cell with flexible machines, assembly lines and buffers. Performance analyses are performed based on qualitative and quantitative properties. For the qualitative analysis, behavioral and structural analyses are applied. Quantitative analyses are conducted using a Petri net simulator.